2016
DOI: 10.23937/2474-1353/1510033
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms in Self-Determined Exercise Motivation. A PhD Thesis Summary

Abstract: human behaviour and how to tailor successful interventions, programs and policies would be to study motivational aspects and self-determination theory [6-8] is a promising framework in this area of research [9,10]. The core message in self-determination theory is that motivation quality and satisfaction of basic psychological needs will fuel the direction of human behaviour and psychological wellbeing [7,8]. According to self-determination theory, psychological need satisfaction will be promoted to the extent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…Motivation depends, among other things, on the perceived outcome benefit and required effort 35. Exercise that is self-determined and that satisfies psychological needs is anticipated to strengthen exercise motivation 36. The participants in this study described strategies both to lower the effort by planning ahead and making exercise easy, and to increase their motivational drive by doing amusing activities or focusing on positive effects.…”
Section: Discussionmentioning
confidence: 99%
“…Motivation depends, among other things, on the perceived outcome benefit and required effort 35. Exercise that is self-determined and that satisfies psychological needs is anticipated to strengthen exercise motivation 36. The participants in this study described strategies both to lower the effort by planning ahead and making exercise easy, and to increase their motivational drive by doing amusing activities or focusing on positive effects.…”
Section: Discussionmentioning
confidence: 99%
“…Previous research has been successful in adopting SDT as a theoretical framework to examine motherhood and wellbeing [28,29]. Lovell, Gordon, Mueller, Mulgrew, and Sharman [29] found that mothers who exercised predominantly in group settings and those who exercised equally in group and individual contexts, experienced significantly higher satisfaction of autonomy and competence basic psychological needs as well as higher self-determined exercise motivation than those exercising predominantly in individual settings.…”
Section: Introductionmentioning
confidence: 99%